2008
DOI: 10.1007/s00419-008-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

Transient response of the crack-tip field in a magnetoelectroelastic half-space with a functionally graded coating under impacts

Abstract: This paper has twofold aims. One is to study the dynamic response of a magnetoelectroelastic half-space with functionally graded coating containing crack at the interface when subjected to sudden impacts. Two different loading positions, where the material and crack surfaces are loaded respectively, are considered. By using the integral transform method, the problem is reduced to solving singular integral equations. Obtained numerical results show that the overshoots of dynamic fracture parameters are strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…0 when the crack is electromagnetically impermeable and vacuum. While the dynamic COD intensity factors are always greater than zero irrespective of the crack being impermeable, vacuum or permeable, implying that the COD intensity factor is more suitable to be a fracture criterion than the stress intensity factor for the dynamic crack growth of magnetoelectroelastic material Peng and Li, 2009). As expected, the dynamic COD intensity factor near the inner crack tip is larger than that near the outer crack tip, meaning that the inner crack tip is easier to grow than the outer crack tip.…”
Section: Numerical Results and Discussionmentioning
confidence: 98%
“…0 when the crack is electromagnetically impermeable and vacuum. While the dynamic COD intensity factors are always greater than zero irrespective of the crack being impermeable, vacuum or permeable, implying that the COD intensity factor is more suitable to be a fracture criterion than the stress intensity factor for the dynamic crack growth of magnetoelectroelastic material Peng and Li, 2009). As expected, the dynamic COD intensity factor near the inner crack tip is larger than that near the outer crack tip, meaning that the inner crack tip is easier to grow than the outer crack tip.…”
Section: Numerical Results and Discussionmentioning
confidence: 98%
“…The transient problem of a magnetoelectro-elastic half-space with a functionally graded coating containing interfacial crack under sudden impacts loads was considered by Peng and Li. 6 They reported that the effects of the gradient index strongly depend on the position of impact loading. Feng et al 7 studied the transient response of an interfacial crack between two dissimilar magneto-electro-elastic layers under impact loadings.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important topics in dynamic fracture mechanics is examining transient response. The transient response of anti-plane cracks at the interface of MEE material was first investigated by researchers who used Laplace-and Fouriertransforms [6][7][8][9][10]. As for the problem of plane cracks at the interface, Zhong et al [11] studied the transient response of two limited permeable collinear cracks in a homogeneous MEE body under impact loadings.…”
Section: Introductionmentioning
confidence: 99%